Chapter 5 Quinoline Alkaloids: CINCHONA Alkaloids (Journal of Chromatography Library, 1984)
This chapter discusses quinoline alkaloids, especially Cinchona alkaloids. High-performance liquid chromatography (HPLC) is applied successfully in the analysis of Cinchona alkaloids that helps deal many problems such as the separation of Cinchona alkaloids in general and the analysis of such alkaloids present in naturally occurring mixtures and in plant material, pharmaceutical preparations, drugs of abuse, food and beverages, and biological fluids. Because of their strong fluorescence under acidic conditions, Cinchona alkaloids have been detected by means of fluorescence detectors. Quinidine has, as an anti-arrhythmic drug, a narrow therapeutic range, and consequently its quantitative analysis in blood, plasma, and serum has been the subject of a series of investigations. Many quinidine metabolites, some of which have a similar activity to quinidine, have been determined, together with quinidine, by the existing methods. A possible interference of other drugs in the analysis of quinidine has been reported, particularly on the interference of quinine.